La inteligencia lingüística y su incidencia en el desarrollo del lenguaje oral de los niños del Jardín de Infantes Fiscal Mixto Amada Agurto de Galarza de la Ciudad de Machala período lectivo 2012-2013. - Mieles Herrera, Maria Isabel (2016)
The present research has as main objective To determine the incidence of linguistic intelligence in the development of oral language of the children of mixed kindergarten fiscal Agurto de Galarza of the City of Machala period 2012-2013. It was done through a mixed study with quantitative, descriptive-deductive, Inductive and Interpretative prevalence, for the collection of information we applied surveys to teachers, parents of relatives and an observation guide to students.